First Description of a Carnivore Protoparvovirus Associated with a Clinical Case in the Iberian Lynx (Lynx pardinus) - Almudena Campoy; Esperanza Gomez-Lucia; Tania Garcia; Elena Crespo; Sonia Olmeda; Felix Valcarcel; Sergio Fandiño; Ana Domenech (Animals)
One of the main threats for the survival of the Iberian lynx is infectious disease. Feline parvoviruses cause often fatal diseases in cats and have been isolated from different species of Felidae and other carnivores. The present study is the first description of a parvoviral sequence isolated from the brain of an Iberian lynx which died four weeks after being transferred to a quarantine centre from a hunting estate in Castilla-La-Mancha (southern border of the Iberian plateau). Four days prior to death, it had developed anorexia and muscle weakness. The nucleotide sequence, at 4589 nt long (GenBank PP781551), was most proximal to that isolated from a Eurasian badger in Italy but also showed great homology with others from cats and other carnivores isolated in Spain and Italy, including that from a cat sequenced by us to elucidate the origin of the infection, which has not been clarified. The phylogenetic analysis of the capsid protein, VP2, which determines tropism and host range, confirmed that the lynx sequence was most proximal to feline than to canine parvoviruses, and was thus typed as Protoparvovirus carnivoran1. More studies, including serology, are needed to understand the pathogenesis of this infection.